2016
DOI: 10.3389/fpls.2016.00047
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Auxin Response Factors (ARFs) in Plants

Abstract: Auxin is a key regulator of virtually every aspect of plant growth and development from embryogenesis to senescence. Previous studies have indicated that auxin regulates these processes by controlling gene expression via a family of functionally distinct DNA-binding auxin response factors (ARFs). ARFs are likely components that confer specificity to auxin response through selection of target genes as transcription factors. They bind to auxin response DNA elements (AuxRE) in the promoters of auxin-regulated gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
268
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(299 citation statements)
references
References 74 publications
6
268
0
5
Order By: Relevance
“…In response to V. dahliae infection, the increased microRNAs included miR160, miR164, miR167 and miR390 that are involved in regulating auxin signals, which play critical roles in almost all aspects of plant developments such as organogenesis, vascular tissue differentiation, apical dominance and root initiation, and in responses to the environmental changes (Chandler 2016; Li et al 2016). Many previous results showed that RNAi pathway is involved in auxin signalling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to V. dahliae infection, the increased microRNAs included miR160, miR164, miR167 and miR390 that are involved in regulating auxin signals, which play critical roles in almost all aspects of plant developments such as organogenesis, vascular tissue differentiation, apical dominance and root initiation, and in responses to the environmental changes (Chandler 2016; Li et al 2016). Many previous results showed that RNAi pathway is involved in auxin signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we demonstrated that auxin-dependent induction of miR847 is involved in regulating meristematic competence by targeting the mRNA of IAA28 to up-regulate auxin signalling (Wang and Guo 2015). Furthermore, many ARF genes are directly regulated by at least one miRNA in response to biotic or abiotic stress, such as ARF6 and ARF8 are targeted by miR167 while ARF10, ARF16 and ARF17 are targeted by miR160 (Chandler 2016; Li et al 2016). ARF2, ARF3 and ARF4 are also targeted by a ta-siRNA, encoded by the TAS3 locus, which is targeted by miR390 (Chandler 2016; Li et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…8; Gray et al, 1999;Dharmasiri et al, 2005;Kepinski and Leyser, 2005; for review, see Enders and Strader, 2015;Salehin et al, 2015;Li et al, 2016). Binding of auxin to TIR1 stabilizes interactions between the SCF TIR1 E3 ubiquitin ligase complex and AUXIN/INDOLE-3-ACETIC ACID (AUX/IAA) repressors, the latter of which are ubiquitinated and subsequently degraded via the 26S proteasome (Gray et al, 1999(Gray et al, , 2001Tiwari et al, 2001;Tian et al, 2003;Dharmasiri et al, 2005;Kepinski and Leyser, 2005;Tan et al, 2007;Maraschin et al, 2009) Korasick et al, 2014; for review, see Guilfoyle and Hagen, 2007;Wright and Nemhauser, 2015).…”
Section: Discussion a Model For The Repression Of Hypocotyl Growth Bymentioning
confidence: 99%
“…Auxin signaling is regulated by IAA cofactors acting in combination with AUXIN RESPONSE FACTOR (ARF) transcriptional partners (Li et al, 2016). We reasoned that IAA factors regulating postembryonic (lateral) root formation (Goh et al, 2012) could be involved in de novo organ formation.…”
Section: Specific Auxin Signaling Factors Regulate De Novo Root Regenmentioning
confidence: 99%